Durability of building and construction sealants and adhesives. 3rd volume - Wolf, A. T. (ASTM International, 2010)
"Twenty-one peer-reviewed papers provide the latest scientific research, gained from laboratory research and field work, in the building and construction industry for all aspects of sealant and adhesive durability."--Publisher's website.
Keywords: Building materials -- Testing -- Congresses.; Sealing compounds -- Testing -- Congresses.; Sealing compounds -- Deterioration -- Congresses.; Adhesives -- Testing -- Congresses.; Adhesives -- Deterioration -- Congresses.; elektronické knihy; electronic books